Associations of liver volume and other markers of hepatic steatosis with all‐cause mortality in the general population. (27th December 2021) - Naeem, Muhammad; Markus, Marcello R. P.; Mousa, Mohammed; Schipf, Sabine; Dörr, Marcus; Steveling, Antje; Aghdassi, Ali; Kühn, Jens‐Peter; Kromrey, Marie‐Luise; Nauck, Matthias; Targher, Giovanni; Völzke, Henry; et al.
Abstract: Aims: We examined the associations between liver volume and other quantitative and qualitative markers of hepatic steatosis with all‐cause mortality in the general population. Methods: We included 2769 German middle‐aged individuals with a median follow‐up of 8.9 years (23, 898 person‐years). Quantitative markers used were serum liver enzymes and FIB‐4 score, while qualitative markers of hepatic steatosis included magnetic resonance imaging (MRI) measurements of liver fat content and total liver volume. Cox proportional hazards models, adjusted for confounding factors, were undertaken to investigate the associations of liver volume and other markers of hepatic steatosis with all‐cause mortality. Results: A larger MRI‐assessed liver volume was associated with a nearly three‐fold increased risk of all‐cause mortality (Hazard Ratio = 3.16; 95% confidence interval 1.88; 5.30), independent of age, sex, body mass index, food frequency score, alcohol consumption and education level. This association was consistent in all subgroups considered (men vs. women; presence or absence of overweight/obesity, metabolic syndrome or diabetes). Higher serum liver enzyme levels and FIB‐4 score were also significantly associated with higher all‐cause mortality in the total population and in all subgroups. No independent associations were found between other quantitative and qualitative markers of hepatic steatosis and the risk of all‐cause mortality. Conclusions: We showed for the first time that larger liver volume was associated with a three‐fold increase in long‐term risk of all‐cause mortality. This association remained significant after adjustment for age, sex, alcohol consumption, obesity and other coexisting metabolic disorders.